Youth Sports and Social Justice: Ensuring Equal Opportunities for All Children in Indonesia’s Sports Development Programs (Indonesian Sports Justice Review, 2025)
Youth sports are a vital part of Indonesia's sports development strategy, yet access to these programs is often unequal, particularly for children from marginalized backgrounds. This paper examines the accessibility and inclusivity of youth sports programs in Indonesia, focusing on the systemic barriers that children from rural, low-income, and indigenous communities face in accessing sports opportunities. The study evaluates government and non-government initiatives aimed at providing equal opportunities for all children, and it explores the role of schools, local communities, and private organizations in promoting social justice in sports development. Through a combination of quantitative data and qualitative interviews, the paper proposes policies to ensure that youth sports are more inclusive, equitable, and accessible to all children, regardless of their socioeconomic status.